2017
DOI: 10.1111/andr.12346
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed testicular expression of the estrogen‐metabolizing enzymes CYP1A1 and COMT in infertile men with primary spermatogenic failure: possible negative implications on Sertoli cells

Abstract: Estradiol (E ) is normally metabolized to hydroxyestradiols and methoxyestradiols by CYP1A1, CYP1B1 and COMT. However, an altered production of these metabolites by a disturbed expression of these enzymes is associated with reproductive and non-reproductive pathologies. In vitro studies suggest that increased hydroxyestradiols and methoxyestradiols intratesticular generation is related to male infertility, but no studies have explored whether infertile men have a disturbed testicular expression of the enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Some earlier studies reported decreased serum levels of T in men with infertility; however, in most of those studies the patients were recruited by their seminal parameters or fertility status [14,24,25]. Similarly to our results, the decrease in T levels was not found in some other studies, where the subjects were selected and grouped according to histological pattern of testicular biopsy [7,12,16,26]. The observed discrepancies may be explained by the fact that there is an extensive overlap between fertile and infertile men hormones' levels which may mask, to some extent, the differences between studied groups depending on selection criteria.…”
Section: Discussionsupporting
confidence: 84%
“…Some earlier studies reported decreased serum levels of T in men with infertility; however, in most of those studies the patients were recruited by their seminal parameters or fertility status [14,24,25]. Similarly to our results, the decrease in T levels was not found in some other studies, where the subjects were selected and grouped according to histological pattern of testicular biopsy [7,12,16,26]. The observed discrepancies may be explained by the fact that there is an extensive overlap between fertile and infertile men hormones' levels which may mask, to some extent, the differences between studied groups depending on selection criteria.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequently, two meta-analysis, included 6 studies involving 1060 cases and 1225 controls, comprehensively evaluated the associations between CYP1A1 rs4646903 polymorphism and male infertility risk, but there results were still inconsistent. [14,15] This inconsistent result may arise from different search strategies, and the 2 meta-analyses do not include all relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…[13] The disturbed testicular expression of CYP1A1 is responsible for producing hydroxyestradiols and/or methoxyestradiols, and the increased intratesticular hydroxyestradiols and methoxyestradiols concentrations could elicit an impaired Sertoli cell function, this could ultimately lead to male infertility. [14] Several single-nucleotide polymorphisms (SNPs) of Cytochrome P4501A1 gene have been identified, including T3801C, T3205C, A2455G. [13] Among them, P4501A1 MspI (3798 T > C; CYP1A1 ∗2A; rs4646903) polymorphism is one of the most-studied single-nucleotide polymorphism (SNP).…”
Section: Introductionmentioning
confidence: 99%
“… 54 55 A recent report showed elevated levels of cytochrome P450, family 1, subfamily A, member 1 (CYP1A1) and Catechol-O-methyltransferase (COMT), which produce hydroxyl-estradiol and methoxy-estradiol, respectively, in testicular biopsies of overweight patients with spermatogenic failure. 56 In addition, these E2 metabolites induce DNA fragmentation in Sertoli cells. 57 Thus, an increase in E2 metabolism rather than decreased E2 production could explain E2 decline without altered testosterone levels.…”
Section: Discussionmentioning
confidence: 99%